A Clinical, Pathological, Epidemiological and Molecular Investigation of Recent Outbreaks of Peste des Petits Ruminants Virus in Domestic and Wild Small Ruminants in the Abu Dhabi Emirate, United Arab Emirates - Hassan Zackaria Ali Ishag; Abdelnasir Mohammed Adam Terab; Yassir Mohammed Eltahir; El Tigani Ahmed El Tigani-Asil; Nasereldien Altaib Hussein Khalil; Esamt Faisal Malik Gasim; Mohd Farouk Yuosf; Saeed Mohamed Saeed Al Yammahi; Asma Mohammed Amer Al Mansoori; Salama Suhail Mohammed Al Muhairi; Zulaikha Mohamed Abdel Hameed Al Hammadi; Asma Abdi Mohamed Shah; et al. (Veterinary Sciences, 2023)
(1) Background: Peste des petits ruminants (PPR) is a highly contagious animal disease affecting small ruminants, leading to significant economic losses. There has been little published data on PPR virus (PPRV) infection in the United Arab Emirates (UAE); (2) Methods: four outbreaks reported in goats and Dama gazelle in 2021 were investigated using pathological and molecular testing; (3) Results: The infected animals showed symptoms of dyspnea, oculo-nasal secretions, cough, and diarrhea. Necropsy findings were almost similar in all examined animals and compliant to the classical forms of the disease. Phylogenetic analysis based on N gene and F gene partial sequences revealed a circulation of PPRV Asian lineage IV in the UAE, and these sequences clustered close to the sequences of PPRV from United Arab Emirates, Pakistan, Tajikistan and Iran; (4) Conclusions: PPRV Asian lineage IV is currently circulating in the UAE. To the best of our knowledge, this is a first study describing PPRV in domestic small ruminant in the UAE.